Endophytes isolated from ginger rhizome exhibit growth promoting potential for Zea mays. Issue 9 (29th July 2018) - Zhang, Yu; Kang, Xia; Liu, Hanjun; Liu, Yihao; Li, Yanmei; Yu, Xiumei; Zhao, Ke; Gu, Yunfu; Xu, Kaiwei; Chen, Cuiping; Chen, Qiang
ABSTRACT: Plant growth promoting bacteria (PGPB) are known to colonize ginger rhizome. A total of 57 strains were isolated and identified by 16S rDNA PCR-RFLP fingerprinting, and were grouped into genera Serratia, Enterobacter, Acinetobacter, Pseudomonas, Stenotrophomonas, Agrobacterium, Ochrobactrum, Bacillus and Tetrathiobacter . Out of 34 representative strains, 14 were positive for indole-3-acetic acid (IAA) production (1.02–49.66 µg ml –1 ), 16 were able to solubilize phosphate (9.3–233.05 µg ml –1 ) and 18 showed siderophore activities (9.47–70.66%). Six representative strains with plant growth promoting (PGP) activities boosted the growth of Zea mays, where not only the plant height, leaf area, and biomass yield were significantly improved, plant N, P and K uptakes were also increased. Plants co-inoculated with both PGPB and chemical fertilizer also showed an increased yield. Our study thus indicates that there is an abundance of endophytic bacteria in ginger rhizome, some of which possess promising capabilities for enhancing the growth of Z. mays and have the potential to serve as bio-fertilizers for crops.